Isoperimetric properties of condenser capacity - Nasser Mohamed M.S.; Vuorinen Matti (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
For compact subsets E of the unit disk D we study the capacity of the condenser (D, E) by means of set functionals defined in terms of hyperbolic geometry. In particular, we study experimentally the case of a hyperbolic triangle and arrive at the conjecture that of all triangles with the same hyperbolic area, the equilateral triangle has the least capacity.